IDENTIFIKASI SENYAWA METABOLIT SEKUNDER EKSTRAK n-HEKSANA DAUN BERWARNA MERAH DARI Syzygium myrtifolium Walp. - Tri Novianti; Chairul Saleh; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2019)
Pucuk Merah (Syzygium myrtifolium Walp.) is one of the plants belonging to the genus Syzygium family Myrtaceae. This study has been carried out to isolate and identify secondary metabolite from red leaf of Syzygium myrtifolium Walp. This research was conducted by extracting Syzygium myrtifolium Walp. leaf with Etanol followed by partition using n-Hexane, n-Hexane extact was separated by Coloum Chromatography with system isokratik. The separation of produce a compounds isolated as white powder. The result of GC-MS analysis was suggested 3 major compounds that 1-Octadecene; bis (2-ethylhexyl) hexanedioic; and bis (2-ethylhexyl) phthalate with a molecules weight in a row 252; 370 and 390.